Understanding community acceptance of a potential offshore wind energy project in different locations: An island-based analysis of 'place-technology fit'. (February 2020) - Devine-Wright, Patrick; Wiersma, Bouke
Abstract: Understanding the factors influencing community acceptance of renewable energy projects such as offshore wind farms is important for achieving a transition to low carbon energy sources. However, to date community acceptance research has concentrated on responses to actual proposals, seeking to explain local objections. 'Upstream' research that investigates the 'place-technology fit' of a potential renewable energy project before it is proposed is scarce, yet can inform technology deployment by taking local knowledge and preferences into account. We address this gap in a study conducted in Guernsey, Channel Islands. Data was collected using a survey (n = 468) co-designed with island policy makers presenting technical, economic and locational details of a potential offshore wind project. Results show that acceptance of the same project design differed significantly across alternative development locations. Regression analyses compared the roles of personal, context and project-related factors in explaining acceptance for each site. Support for using wind energy for local electricity supply was the most important predictor of acceptance, and this variable mediated the relationship between island energy security and community acceptance. We conclude that place matters for community acceptance and that security and autonomy are co-benefits of local renewable energy projects that deserve further research. Highlights: Analysis of 'place-technology fit' can inform the siting of wind projects. Acceptance of the same project design differed across development locations. Support for using wind for local energy supply was the most important predictor. Role of security and autonomy in fostering acceptance deserves further research.